China’s One Belt One Road (OBOR) initiative and the Muslim world - Rabeya, Sumaiya; Hossain, Ishtiaq (The Council for Social and Economic Studies. Washington DC, 2019)
Ever since President Xi Jinping assumed the office of president of the People’s Republic of China (PRC) in March 2013, Beijing has followed an active foreign policy, abandoning President Hu Jintao’s (2003-2013) “low profile” foreign policy. Under President Xi’s leadership, in addition to claiming full sovereignty over the disputed islands in the South China Sea, and, as part of building good relationship with its neighbours, Beijing has been pursuing a new policy of improving and developing close economic and trade relationship with the neighbouring countries. The One Belt, One Road (OBOR) policy initiative is at the centre of that policy. OBOR revives the ancient Silk Route, a vast and ancient network of trade routes linking China’s merchants with those of Central Asia, the Middle East, Africa and Europe. The modern OBOR connects Muslim-majority states in Central Asia, Pakistan, Bangladesh, Malaysia, Indonesia and others as China openingg up new trading opportunities. The Maritime Silk Route connects China with Malaysia and Indonesia. It is likely that OBOR would play a key role in the development of China’s economic and political relations with members of the Muslim world. Through document and thematic analysis, this paper seeks to discuss the One Belt One Road initiative, its origin, structure and scope and also provide a historical background. This paper will further explain the influence of Islam on the ancient Silk Road that the OBOR is inspired from and the response of the Muslim world, in particular,Malaysia, Pakistan and Bangladesh to OBOR.